Quantification of XRCC and DNA-PK proteins in cancer cell lines and human tumors by LC–MS/MS. (November 2014) - Myers, Matthew V; Maxwell, Stephen E; Wang, Xiaomin
Background: The x-ray repair cross-complementing (XRCC) proteins and a catalytic subunit of nuclear DNA-dependent serine/threonine protein kinase (DNA-PK) play important roles in cancer biology. Understanding the protein expression levels allows us to reconstruct in vivo functionality and to qualify protein biomarkers.Methods & results: XRCC and DNA-PK proteins in human cancer cells and tumor tissues have been identified and quantified by selected peptides using NanoLC and high-resolution mass spectrometry. The stable isotope-labeled full-length protein XRCC4 ([ 13 C6, 15 N4 ]-arginine and [ 13 C6, 15 N2 ]-lysine) uses as the internal standard.Conclusion: The assay range is 0.140–450 fmol (coefficient of variation: 25%) for XRCC4 in bovine serum albumen. The quantitative protein expression levels for XRCC and DNA-PK in HeLa, Ramos and HEK-293 cells and tumor tissues (lung and lymphoma) are reported